المشكلات البيئية لدى الطلبة المعلمين وعلاقتها بوعيهم البيئي - حافظ، محمد رحيم; فهد، جواد كاظم (جامعة بغداد - كلية التربية ابن رشد, 2016)
يهدف هذا البحث إلى التعرف على المشكلات البيئية لدى طلبة معاهد إعداد المعلمين وعلاقتها بوعيهم البيئي مجتمع البحث يتكون من طلبة معاهد المعلمين/ بغداد الكرخ والرصافة، وقد استخدم الباحثان المنهج الوصفي، إذ قام الباحثان بإعداد اختبار للمشكلات البيئية تألف من (٢٠) فقرة من نوع الاختيار من متعدد، وتم حساب الصدق والثبات له، كما استخدم الباحثان مقياساً جاهزاً للوعي البيئي تألف من (٣٠) فقرة، أظهرت نتائج البحث امتلاك الطلبة المعلمين في معاهد إعداد المعلمين فهما للمشكلات البيئية بدرجة متوسط ووعياً بيئياً بدرجة جيد جداً، ووجود علاقة ذات دلالة إحصائية بين فهم الطلبة المعلمين للمشكلات البيئية ووعيهم البيئي، وقدم الباحثان جملة من التوصيات والمقترحات التربوية التي لها علاقة بالطلبة المعلمين.
The current research aims to identify environmental problems in the students of preparation of teachers institutes, and their relevance to promote environmental awareness. The research community is consist of students of institutes Baghdad Karkh and Rusafa. Two researcher is used the descriptive approach. The researchers prepare test of environmental problems consisted of (20) items of multiple choice where find reliability and validity identified. The researchers used a prepared measure of environmental awareness consisted of (30) items. The Results of Search showed that Training Teachers have understanding of environmental problems with average degree and very good in environmental awareness, and it is a statistically significant relevance between the understanding of environmental problems and the environmental awareness. The researchers conclude a number of recommendations and educational proposals that have to do with Training Teachers.
Keywords: البيئة -- الوعي البيئي -- المشكلات البيئية -- الطلبة المعلمين